The Influence of Using Banyuwangi Local History Sources on Awareness History Student Senior High School August 17, 1945 Banyuwangi - miskawi; Dhalia Soetopo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The problems that will be studied in this research are: (1) How are local historical sources used in history learning in high school 17 August 1945 Banyuwangi?, (2) What is the historical awareness of high school students? 17 August 1945 Banyuwangi?, (3) Is there an influence of the use of local historical sources on high school students' historical awareness? 17 August 1945 Banyuwangi? Population research is student SENIOR HIGH SCHOOL 17 August 1945 Banyuwangi. In taking samples in the field using random sampling techniques by taking a sample of 20 students from each State High School in Banyuwangi. The variables of this research are: use of local historical sources and historical awareness of high school students 17 August 1945 Banyuwangi. Data uses a questionnaire (questionnaire). Research data was analyzed using descriptive percentage techniques and regression analysis. The results of this research show that utilization local history sources, Historical Awareness in SMA 17 August 1945 Banyuwangi is included in the criteria as quite good. The results of the regression analysis show that for every increase in the use of local historical sources by 1 unit, it increases students' historical awareness was 0.51. Meanwhile, the magnitude of the influence The use of local historical sources on students' historical awareness is 24.1%, the remainder is influenced by other variables not included in this this research. Based on the research results, there is an influence of the use of local historical sources in Banyuwangi Regency on the historical awareness of high school students 17 August 1945, Banyuangi Regency.